Biologi Molekuler Human Papilloma Virus - Maya Savira (Jurnal Ilmu Kedokteran, 2017)
Persistent infection of the high-risk group Human Papilloma Virus (hrHPV) has been known to cause cervical cancer. Currently cervical cancer still ranks as the number two of most malignant disease in women. The infection of HPV that lead to cancer cells to form can be known through the structure of the HPV virus itself and what particles in the virus play a role in initiating the carcinogenic process of its host cell.